2016
DOI: 10.4067/s0718-16202016000200010
|View full text |Cite
|
Sign up to set email alerts
|

VOLCANIC MATERIALS AS CARRIERS FOR THE FORMULATION OF MYCOINSECTICIDES USING THE FUNGUS Beauveria bassiana

Abstract: V.E. Sy, S. Schalamuk, A.C. Scorsetti, and I.L. Botto. 2016. Volcanic materials as carriers for the formulation of mycoinsecticides using the fungus Beauveria bassiana. Cien. Inv. Agr. 43(2):273-282. Improvements in the formulation of biological insecticides are crucial to increase their stability and competitiveness in the market. The aim of this work was to evaluate the use of volcanic materials with different hydric retention capacities to increase the thermotolerance of B. bassiana conidia. Two pyroclastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(30 reference statements)
1
0
0
Order By: Relevance
“…This suggests that conidia were still viable with a germination rate was 70%. A similar decreasing pattern of conidia viability was also reported by Sy, et al [38], who observed the germination percentage of B. bassiana was reduced by 20-50% within 30 days of storage at 30 𝑜 C. In contrast, a high conidia germination rate, more than 85%, were retained in the samples stored at 4 𝑜 C for up to 24 months [39]. The germination rate was influenced by an interaction between storage temperature and storage time.…”
Section: Storage Stability Of the B Bassiana Conidia At Room Temperaturesupporting
confidence: 85%
“…This suggests that conidia were still viable with a germination rate was 70%. A similar decreasing pattern of conidia viability was also reported by Sy, et al [38], who observed the germination percentage of B. bassiana was reduced by 20-50% within 30 days of storage at 30 𝑜 C. In contrast, a high conidia germination rate, more than 85%, were retained in the samples stored at 4 𝑜 C for up to 24 months [39]. The germination rate was influenced by an interaction between storage temperature and storage time.…”
Section: Storage Stability Of the B Bassiana Conidia At Room Temperaturesupporting
confidence: 85%